1980
DOI: 10.1021/jo01312a027
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of acyl anion equivalents by carbon-13 Fourier transform nuclear magnetic resonance

Abstract: The vinyl anions derived from 2,3-dihydrofuran, 2,3-dihydro-4fi-pyran, and ethoxyethene have been examined by carbon-13 FT NMR. The vinyl C-H coupling constants (V13c_ih) have been measured for the ethers and the anions. Observation of vinyl anions derived from vinyl ethers is readily accomplished with carbon-13 NMR.While all carbon resonances are shifted upon formation of the anion the most obvious effect is the large (56-61 ppm) downfield shift of the vinyl carbon bonded to lithium. In no case was allylic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 1 publication
1
13
0
1
Order By: Relevance
“…In the current study, both the microsolvation model and the mixed discrete-continuum model seem better in reproducing the experimental results. It is well-known that vinylic lithiation is preferred experimentally for DHF and DHP, 8 Keywords: Density functional theory; Microsolvation; Continuum solvation; Mixed discrete-continuum solvation; Transition states. generally believed that both the electronegative vinyl ether oxygen and precomplexation affect lithiation regioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, both the microsolvation model and the mixed discrete-continuum model seem better in reproducing the experimental results. It is well-known that vinylic lithiation is preferred experimentally for DHF and DHP, 8 Keywords: Density functional theory; Microsolvation; Continuum solvation; Mixed discrete-continuum solvation; Transition states. generally believed that both the electronegative vinyl ether oxygen and precomplexation affect lithiation regioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 Ha nd 13 C spectra of 1&THF in [D 8 ]THF at À60 8C, À80 8Cand À100 8Cdisplayed only one set of signals. In addition, the 1 J(C2,C3)c oupling is reduced in magnitudeb y2 7Hzasc ompared to that of 7.S imilar down-field shifts and/orr eductionso ft he magnitude of the coupling constant have been described for vinyllithium, [25][26][27] ethoxyvinyllithium, [28] halogen vinyllithiums [25] and aryl vinyllithiums. The variations in the chemical shifts of 1&THF on going from room temperature to low temperatures were only minor.F or example, the 13 CNMR signal of C2 experienced ah igh-field shift of Dd = À0.8 ppm, while the signal of C3 showed at emperaturedependentv ariation of Dd = À2ppm.…”
Section: Synthesis Of Vinyl Sulfoximinesmentioning
confidence: 86%
“…The variations in the chemical shifts of 1&THF on going from room temperature to low temperatures were only minor.F or example, the 13 CNMR signal of C2 experienced ah igh-field shift of Dd = À0.8 ppm, while the signal of C3 showed at emperaturedependentv ariation of Dd = À2ppm. [25][26][27][28][29][30] Thus, the p-bond of 1 is similarly polarized as in other vinyllithiums despite the presence of the sulfonimidoyl group. Thus, it is concluded that 1&THF exists in THF preferentially as am onomer on the basis of the NMR spectroscopic and cryoscopicresults.…”
Section: Synthesis Of Vinyl Sulfoximinesmentioning
confidence: 99%
“…The solvents were then removed completely, and the addition of pentane precipitated the crude product as a brown solid, which was recrystallized from toluene/pentane to give the required complex as a buff-coloured solid (50 mg, 35%). 1 Preparation of (2-2 H 1 )-2,3-Dihydrofuran by a Modified Procedure [28]. In a dry Schlenk tube, BuLi (2.5m in hexane, 13 ml) was added rapidly to a mixture of freshly distilled 2,3-dihydrofuran (2 g, 28.5 mmol) and tmeda (0.6 g), whereupon vigorous effervescence and precipitation occurred.…”
Section: Experimental Partmentioning
confidence: 99%